2011
DOI: 10.1021/ic202535e
|View full text |Cite
|
Sign up to set email alerts
|

Formation of a Uranium Trithiocarbonate Complex via the Nucleophilic Addition of a Sulfide-Bridged Uranium Complex to CS2

Abstract: The uranium(IV)/uranium(IV) μ-sulfide complex [{(((Ad)ArO)(3)N)U}(2)(μ-S)] reacts with CS(2) to form the trithiocarbonate-bridged complex [{(((Ad)ArO)(3)N)U}(2)(μ-κ(2):κ(2)-CS(3))]. The trithiocarbonate complex can alternatively be formed in low yields from low-valent [(((Ad)ArO)(3)N)U(DME)] through the reductive cleavage of CS(2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 16 publications
3
53
1
Order By: Relevance
“…The main position (55% occupancy) leads to aC ÀSd istance of 1.748 (15),t he minor position (45 %o ccupancy) leads to as horter CÀSd istance of 1.630 (16).T he CÀSd istances remain in the range of previously reported trithiocarbonate complexes. [26,27] There are two previous reports of trithiocarbonatec omplexes containing fe lements, [28,29] but the complex [Eu-(BPA)(CS 3 )(dmso) 2 ]i st he first example of at rithiocarbonate complex containing a4fe lement. Moreover, only three examples of CS 2 reduction by lanthanide complexes have been reported before.T he reduction of CS 2 by Eu 2 + and Yb 2 + tetrasiloxide complexes has been reported by our group [5c] and was found, by 13 CNMR studies, to afford trithiocarbonate and tetrathioxalate products in different ratios depending on the Ln 2 + ion.…”
Section: Reactivitymentioning
confidence: 99%
“…The main position (55% occupancy) leads to aC ÀSd istance of 1.748 (15),t he minor position (45 %o ccupancy) leads to as horter CÀSd istance of 1.630 (16).T he CÀSd istances remain in the range of previously reported trithiocarbonate complexes. [26,27] There are two previous reports of trithiocarbonatec omplexes containing fe lements, [28,29] but the complex [Eu-(BPA)(CS 3 )(dmso) 2 ]i st he first example of at rithiocarbonate complex containing a4fe lement. Moreover, only three examples of CS 2 reduction by lanthanide complexes have been reported before.T he reduction of CS 2 by Eu 2 + and Yb 2 + tetrasiloxide complexes has been reported by our group [5c] and was found, by 13 CNMR studies, to afford trithiocarbonate and tetrathioxalate products in different ratios depending on the Ln 2 + ion.…”
Section: Reactivitymentioning
confidence: 99%
“…This is in line with previous reports on CS 2 activation with either Sm II or U III complexes, where the low kinetic stability of the formed CS was already underlined. [29][30][31] In the same way, on the basis of previous work, [29] the formation of thiooxalate is predicted to involve a relatively high barrier preventing this reactivity. Finally, the C-S bond formation was investigated.…”
Section: Resultsmentioning
confidence: 65%
“…This C-S bond formation is reminiscent of the C-O bond formation reported by Castro et al in carbonate formation in U III and Sm II chemistry. [30][31][32][33] How-ever, in the latter, after C-O bond formation, C-O bond cleavage occurred to form a CO molecule. Interestingly, in this study (Figure 3), C-S bond breaking is not observed, which strengthens the argument of the lack of stability of the CS molecule.…”
Section: Resultsmentioning
confidence: 99%
“…The insertion of CS 2 into U–element bonds is exceedingly rare,7, 12 and only one example has been reported for UC bonds, involving the U 3+ alkyl complex [Tp* 2 U(CH 2 Ph)], which yields 10 7a. Complex 6 is therefore the first example of the insertion of CS 2 into a U 4+ alkyl bond.…”
Section: Discussionmentioning
confidence: 99%